Mulching as a Water-saving Technique in Arid and Semi-arid Regions - Wasifhy, Mohammad Khan; Durrani , Jahid Ahmad; Barai, Shah Mahmood (Journal of Natural Sciences – Kabul University, 2024)
Water sources become scarce in dry and semi-dry areas and farmers in these areas are seeking techniques that solve the problem. One of those is mulch use as water-saving method. For this valuable issue, here is a review paper from sufficient research papers to see its results for the solving of the problem. Mulch has many benefits such as; soil moisture retention, decreasing soil erosion and hardness, managing soil temperature, decreasing diseases and pests, controlling weeds, and plants growth, increasing the yield, controlling salts effect, and improving soil productivity, besides that, sometimes have negative effect which is not considerable compare to its benefits. Those constraints could be decreasing soil pH, allelopathic effects, competition for sources, the occurrence of diseases and pests, flaming, Nitrogen deficiency, and weeds growing. Mulch has more types due to its source materials some are not economical and some are not applicable and seeing this characteristic, mulch suitability is needed. Mulching materials are divided into two categories such as organic materials mulch which is decomposable and non-organic materials such as plastics and sand mulch which is not decomposable. Based on research results, mulches election should be on, material type, ecological location, color, thickness, having pores, cost-effectiveness, suitability for growth, and accessibility to the area and field. But for high-yield and row-growing crops plastic mulch is recommended because it is light, easy to manage and covers soil better compared to organic mulch.